Upper airway resistance syndrome: evaluation of patients with excessive day time sleepiness non-invasively - Ingle, Vaibhav Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Upper airway resistance syndrome (UARS) is a recent concept introduced among sleep disordered breathing (chronic snoring and Obstructive sleep apnea) disorders. UARS also presents with excessive daytime sleepiness (EDS), which is associated with impaired social functioning, work performance and driving ability. However, UARS is not merely a continuum between chronic snoring and obstructive sleep apnea (OSA). Not only UARS patients have equal gender distribution and thin body habitus but they also do not fulfil Polysomnographic criteria of OSA. UARS diagnosis requires oesophageal manometry for diagnosing increased respiratory efforts against increased upper airway resistance (without complete cessation of airflow or hypoxia) and correlating it with EEG arousals to mark an event. Oesophageal manometry is invasive and uncomfortable, therefore, non-invasive means are desirable for evaluation of UARS. The aim of the study is to evaluate the patients with EDS for UARS non-invasively. Methods: 25 consecutive patients with EDS (Epworth Sleepiness Score >9) visiting sleep clinic at a tertiary level hospital in North India were enrolled after informed consent. It was a non-blinded, interventional trial. All enrolled patients underwent nocturnal polysomnography using VIASYS healthcare sleep screen apnea screen cardio polysomnography machine. After PSG, those patients satisfying criteria for OSA were not analysed further. In remaining patients, greater than 10 alpha EEG arousals/h (Spontaneous Arousals) along with flattening or plateau of inspiratory flow contour (by nasal cannula) was employed to diagnose UARS non-invasively. Epi-info software was used in statistical analysis. Results: Out of 25 patients with EDS, 60% (15) were diagnosed as OSA based on Apnea-Hypopnea Index (AHI) > 10/hr. Among 15 OSA patients,10 patients had severe (AHI >30); 2 had moderate (AHI 15-30) and 3 had mild OSAS (AHI 10-15). Only one patient was provisionally diagnosed as UARS based on nasal air flow graph and spontaneous arousals/hr >10. Conclusions: Upper airway resistance syndrome (UARS) is a distinct sleep disorder from obstructive sleep apnea syndrome (OSAS) with unique pathophysiology and it need be evaluated in all patients with unexplained arousals.